2017
DOI: 10.1016/j.ecoser.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Going green? Ex-post valuation of a multipurpose water infrastructure in Northern Italy

Abstract: HighlightsWe use a CV approach to estimate how households value a green infrastructure.As a case study we consider the Gorla Maggiore water park (Northern Italy).We find a positive willingness to pay for the green infrastructure (16.5 euros/hh/y).Building of the green infrastructure can be rationalized based on a cost-benefit criterion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 45 publications
0
24
0
2
Order By: Relevance
“…Income was found to have a statistically positive effect on WTP [15,16,51]. A number of studies indicated the significance of education and culture on the assessment of GI.…”
Section: Explanatory Variables: Demand Needs and Wants Arising Frommentioning
confidence: 95%
See 3 more Smart Citations
“…Income was found to have a statistically positive effect on WTP [15,16,51]. A number of studies indicated the significance of education and culture on the assessment of GI.…”
Section: Explanatory Variables: Demand Needs and Wants Arising Frommentioning
confidence: 95%
“…The results indicated that people were willing to pay up to £10.56, or 2% of monthly rent, for locations with a high-quality GI environment. Italian households were found to be willing to pay extra charges of approximately 6.5 euros for GI in the area and a premium of 16.5 euros per year for being surrounded by parkland [15]. Results from research conducted in Hong Kong suggested that households were prepared to pay an extra charge of nearly 10 USD per year to recover and maintain green space areas.…”
Section: The Dependent Variablementioning
confidence: 99%
See 2 more Smart Citations
“…The value residents place on ecosystem services associated with GI were quantified from Gorla Maggiore (Italy) finding that households are willing to pay from 6.3 to 7.1 euros per year for GI (compared to conventional grey), with up to 16.5 euros if the area is made into a park (Reynaud et al, 2017). The potential of using a "pay-forsuccess" model to fund water authority initiatives, specifically for green infrastructure, is demonstrated for DC Water (Appel et al, 2017).…”
Section: Planning and Ecosystem Service Evaluationmentioning
confidence: 99%